Indices of heart rate variability are not associated with obesity in patients 30-60 years of age without chronic noncommunicable diseases - Olga N. Dzhioeva; Elizaveta A. Rogozhkina; Vladimir A. Shvartz; Elena N. Shvartz; Anton R. Kiselev; Oxana M. Drapkina (Russian Open Medical Journal)
Objective –– to compare heart rate variability (HRV) in patients aged 30-60 years without chronic noncommunicable diseases (CNCDs) with and without obesity. Methods –– The groups of obese (n=43) and nonobese (n=28) patients without CNCDs ranged 30 through 60 years of age. We assessed the conventional HRV indices according to the clinical guidelines, as well as the synchronization index (S) for low-frequency (LF) oscillations evaluated from HRV and photoplethysmogram (PPG). Results –– No statistically significant differences in HRV indices and S index were detected between the study groups. Conclusion –– HRV indices and synchronization of LF oscillations detected from HRV and PPG were not significantly associated with obesity in patients aged 30-60 years without CNCDs.